Assessment of interaction effects between wave energy converters - Sakleshpur Lokesh Gowda, Uday Rajdeep; Khedkar, Hrishikesh Nitin (My University, 2023)
Wave energy is one of the abundant renewable energy sources in nature. The technology to harness wave energy is at technology readiness level TRL 7-8 (stage 4), i.e., single full-scale prototypes have been tested at sea according to the development steps defined by the European Marine Energy Centre. The next development goal is the wave park, in other words an array of wave energy converters (WECs). This thesis focuses on C4, the heaving point absorber WEC developed with the specifications from CorPower Ocean, and how it should be arranged in wave parks to maximize the harnessing of wave energy. While it is important to improve the efficiency of the WEC, such a system is better utilized in groups forming an array of WECs, hence it is important to study the behaviour of such an array. One of the key challenges in modelling a WEC array (a.k.a. wave park) is the interaction effects between the WECs. Studies have shown that interaction effects between WECs are important to optimize the power output of the wave park. The aim of this thesis is to model two different WEC arrays of 16 WECs, grouped as 4x4 and 8x2 WECs, and study the interaction effects for different environmental conditions. The study investigates the characteristics of the two arrays by varying the distance between the WECs, the variation of the damping coefficient of the power take off (PTO) system for different environmental conditions. A coupled hydrodynamic and structural response analysis is carried out using the DNV software SESAM. The power absorbed for all simulated conditions are evaluated and a methodology is proposed for the preliminary design analysis of wave parks. From this study, it is concluded that the interaction effects play a significant role in the performance of the WECs. The power produced from wave parks depends on several factors and they must be systematically included in preliminary design studies. The optimization of the WEC array also depends on limiting the parameters to installation location. The methodology used in this study proved to be a good tool that incorporated both interaction effects and the design parameters. Examining these behaviours is crucial to unlocking and optimizing the full potential of wave parks.
Keywords: array; heaving point absorber; power absorption; wave energy converter; wave energy parks; wave interaction effects